Mitochondrial functions and melatonin: a tour of the reproductive cancers - Chuffa, Luiz Gustavo de Almeida [UNESP]; Seiva, Fábio Rodrigues Ferreira; Cucielo, Maira Smaniotto [UNESP]; Silveira, Henrique Spaulonci [UNESP]; Reiter, Russel J.; Lupi, Luiz Antonio [UNESP] (Springer Nature, 2019)
Cancers of the reproductive organs have a strong association with mitochondrial defects, and a deeper understanding of the role of this organelle in preneoplastic–neoplastic changes is important to determine the appropriate therapeutic intervention. Mitochondria are involved in events during cancer development, including metabolic and oxidative status, acquisition of metastatic potential, resistance to chemotherapy, apoptosis, and others. Because of their origin from melatonin-producing bacteria, mitochondria are speculated to produce melatonin and its derivatives at high levels; in addition, exogenously administered melatonin accumulates in the mitochondria against a concentration gradient. Melatonin is transported into tumor cell by GLUT/SLC2A and/or by the PEPT1/2 transporters, and plays beneficial roles in mitochondrial homeostasis, such as influencing oxidative phosphorylation and electron flux, ATP synthesis, bioenergetics, calcium influx, and mitochondrial permeability transition pore. Moreover, melatonin promotes mitochondrial homeostasis by regulating nuclear DNA and mtDNA transcriptional activities. This review focuses on the main functions of melatonin on mitochondrial processes, and reviews from a mechanistic standpoint, how mitochondrial crosstalk evolved in ovarian, endometrial, cervical, breast, and prostate cancers relative to melatonin’s known actions. We put emphasis on signaling pathways whereby melatonin interferes within cancer-cell mitochondria after its administration. Depending on subtype and intratumor metabolic heterogeneity, melatonin seems to be helpful in promoting apoptosis, anti-proliferation, pro-oxidation, metabolic shifting, inhibiting neovasculogenesis and controlling inflammation, and restoration of chemosensitivity. This results in attenuation of development, progression, and metastatic potential of reproductive cancers, in addition to lowering the risk of recurrence and improving the life quality of patients.
Keywords: Breast cancer; Cervical cancer; Endometrial cancer; Melatonin; Mitochondrial function; Ovarian cancer; Prostate cancer